Progressive multifocal leukoencephalopathy associated with chemotherapy induced lymphocytopenia in solid tumors – case report of an underestimated complication - Mayr, Patrick; Lutz, Mathias; Schmutz, Maximilian; Hoeppner, Jens; Liesche-Starnecker, Friederike; Schlegel, Jürgen; Gaedcke, Jochen; Claus, Rainer (Frontiers in Oncology, 2022)
BACKGROUND: JC virus reactivation causing progressive multifocal leukoencephalopathy (PML) occurs preferentially in human immunodeficiency virus (HIV) positive individuals or patients suffering from hematologic neoplasms due to impaired viral control. Reactivation in patients suffering from solid malignancies is rarely described in published literature. CASE PRESENTATION: Here we describe a case of PML in a male patient suffering from esophageal cancer who underwent neoadjuvant radiochemotherapy and surgical resection in curative intent resulting in complete tumor remission. The radiochemotherapy regimen contained carboplatin and paclitaxel (CROSS protocol). Since therapy onset, the patient presented with persistent and progredient leukopenia and lymphopenia in absence of otherwise known risk factors for PML. Symptom onset, which comprised aphasia, word finding disorder, and paresis, was apparent 7 months after therapy initiation. There was no relief in symptoms despite standard of care PML directed supportive therapy. The patient died two months after therapy onset. CONCLUSION: PML is a very rare event in solid tumors without obvious states of immununosuppression and thus harbors the risk of unawareness. The reported patient suffered from lymphopenia, associated with systemic therapy, but was an otherwise immunocompetent individual. In case of neurologic impairment in patients suffering from leukopenia, PML must be considered – even in the absence of hematologic neoplasia or HIV infection.